Schistosoma haematobium infections among schoolchildren in central Sudan one year after treatment with praziquantel - Ahmed Abedaziz M (Parasites & Vectors, 2012)
Abstract Background Chemotherapy with praziquantel (PZQ) is the mainstay of schistosomiasis control. However, there are recent concerns about tolerance or resistance to PZQ, so that monitoring its efficacy in different settings is required. Methods A longitudinal study was conducted to evaluate the impact of PZQ for the treatment of Schistosoma haematobium infection among schoolchildren at Al Salamania, Central Sudan. Parasitological examinations for S. haematobium were performed in a cohort of schoolchildren (6–15 years of age) before and 1 year after treatment with a single dose of PZQ 40 mg/kg. Results Out of 562 (309 boys and 253 girls) schoolchildren recruited from three elementary schools, 420 completed one longitudinal dataset that comprised of data from two time points; baseline, and follow-up 1 year after treatment with a single dose of PZQ 40 mg/kg for S. haematobium infection. A single dose of PZQ significantly reduced the prevalence of S. haematobium infection by 83.3% (from 51.4% to 8.6%) and the geometric mean intensity of infection of positive individuals by 17.0% (from 87.7 to 72.8 eggs/10 ml of urine) 1 year after treatment. While there was no significant difference in the reduction of the prevalence of S. haematobium infection between the gender or age groups, there was a significantly higher reduction of intensity of S. haematobium infection among girls in comparison with boys. Conclusion There was a significant reduction of S. haematobium infection 1 year after PZQ treatment in this setting.